Accessibility of Public Open Space for Children with Disabilities (Case study: Gajah Wong Park and Denggung Park, D.I. Yogyakarta) - Andi Al-Mustagfir Syah; Wiryono Raharjo (Talenta Publisher, 2019)
A group of children experience disability in segregation conditions, namely the status of individuals who have difficultie / are denied access to public services. Many of them are marginalized and it is difficult to access existing facilities in the city. The aim of the study was to find out what application of accessibility services tended to have been implemented and which was still less applied in urban public open space planning. In terms of efforts to achieve the right of equality and fulfillment of services in the public open space for children with disabilities. The method used in this study is qualitative and this research is descriptive. by collecting data related to elephant wong parks and denggung parks. then the data were analyzed using the Miles and Huberman analysis method, namely the analysis method with 3 stages. 1) data reduction 2) data display 3) conclution. The results of this study indicate that the application of accessibility services in terms of four criteria, namely: ease, usability, safety, and independence. Ease is still a priority in the design of public open space and independence is still a part that has not been well considered, so that public open space cannot be used independently for persons with disabilities. Keyword: Accessibility, Open Space, Disabled child